2017
DOI: 10.1038/s41598-017-05355-4
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomics of an in vitro digested α-Gal carrying protein revealed IgE-reactive peptides

Abstract: The mammalian carbohydrate galactose-α1,3-galactose (α-Gal) causes a novel form of food allergy, red meat allergy, where patients experience severe allergic reactions several hours after red meat consumption. Here we explored gastric digestion of α-Gal glycoproteins using an in vitro model. Bovine thyroglobulin (BTG), a typical α-Gal carrying glycoprotein, was digested with pepsin. The resulting peptides were characterised by SDS PAGE, immunoblot and ImmunoCAP using sera from 20 red meat allergic patients. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
4
20
0
Order By: Relevance
“…Of importance, the major peptides carrying the α-Gal epitope were detected at molecular weights between 25 and 55 kDa, although faintly stained, implicating a prolonged survival of proteins during gastric digestion and a prolonged availability for uptake by intestinal cells. Moreover, we have previously shown that α-Gal containing peptides resulting from pepsinolysis are allergenic, reinforcing their role as clinically relevant food allergens [18]. These findings are in accordance with a previous study that demonstrated that glycosylation protects the egg allergen ovomucoid from pepsinolysis [19].…”
Section: Discussionsupporting
confidence: 91%
“…Of importance, the major peptides carrying the α-Gal epitope were detected at molecular weights between 25 and 55 kDa, although faintly stained, implicating a prolonged survival of proteins during gastric digestion and a prolonged availability for uptake by intestinal cells. Moreover, we have previously shown that α-Gal containing peptides resulting from pepsinolysis are allergenic, reinforcing their role as clinically relevant food allergens [18]. These findings are in accordance with a previous study that demonstrated that glycosylation protects the egg allergen ovomucoid from pepsinolysis [19].…”
Section: Discussionsupporting
confidence: 91%
“…Endoglycosidase H cleaves the linkage between the two N-acetylglucosamine residues in the diacetylchitobiose unit of high mannose and some hybrid types, but not of complex types of N-glycans, while PNGaseF cleaves N-glycans between the innermost GlcNAc and asparagine of all N-glycans [55][56][57]. The α-Gal epitope has been reported as being part of both complex and/or hybrid N-glycans 58. Hence, Endoglycosidase H has a limited specificityand is less suitable for an overall deglycosylation of N-glycans and, thus, for the α-Gal removal, in comparison with PNGaseF.…”
mentioning
confidence: 99%
“…Allergen‐specific basophil degranulation was analysed by monitoring the basophil activation markers CD203c and CD63, as previously described . Heparinized venous blood samples from five red meat‐allergic patients, one atopic birch‐allergic patient, and one nonallergic control were analysed with HSA‐α‐Gal, HSA‐B‐antigen (Dextra Lab) and HSA.…”
Section: Methodsmentioning
confidence: 99%